POLA PENDIDIKAN KARAKTER KEMANDIRIAN ANAK BERKEBUTUHAN KHUSUS TUNANETRA PADA PANTI ASUHAN TUNANETRA TERPADU AISYIYAH PONOROGO - Wahyu Dewi Yuliana; Ardhana Januar Mahardhani; Prihma Sinta Utami (EDUPEDIA, 2019)
This study aims to (1) find out and describe the implementation of character independence education for children with visual impairments in the Ponorogo Regency Aisyiah Integrated Blind Home, (2) to create a pattern of character education of children with special needs visually impaired in the Ponorogo Regency Aisyiah Integrated Blind Home. This study uses a qualitative method with a groundet theory approach. The research was carried out at the Aisyiyah Ponorogo Integrated Blind Orphanage with informants, namely the head of the orphanage, the board of education and blind children. Procedure for collecting data using interview procedures, observation and documentation. Data analysis in this study uses data collection, data reduction, data display, verification and confirmation of conclusions.The results of the research obtained from this study are: (1) The implementation of character independence education at the Aisyiyah Ponorogo Integrated Blind Orphanage has been well implemented, in accordance with the four characteristics of independence. (2) The character education pattern of independence of children with khusust needs unanetra in the Aisyiyah Ponorogo Integrated Blind Orphanage is divided into four, namely: a) Initial assessment is carried out in the form of recording the identity of foster children and their families; b) OMD (basic mobility orientation) in the form of daily activities training c) Exploring talent to train and develop talents possessed by foster children and; d) OML (Advanced mobility orientation) activities related to activities carried out in the community.